Central nervous system manifestations in HIV: magnetic resonance imaging pictorial review - Gupta, Lipika; Gupta, Archit (International Journal of Research in Medical Sciences, 2023)
Human immunodeficiency virus (HIV) is a member of the Retroviridae (retrovirus) family. It is associated with immunodeficiency, neurological diseases and neoplasms. With the use of antiretroviral therapy (ART), the prognosis of people who are infected with HIV has improved, and the incidence of HIV-related central nervous system (CNS) diseases has markedly decreased. In spite of that the mortality from HIV-related CNS diseases remains significant. Magnetic resonance imaging (MRI) has improved the perspective for people with HIV with the help of early diagnosis and prompt treatment. There are various conditions which come under the spectrum of CNS manifestations of HIV for e.g., HIV encephalopathy, progressive multifocal leukoencephalopathy (PML), HIV-related primary CNS lymphoma (PCNSL), CNS toxoplasmosis, other diseases caused by opportunistic infections like CNS cryptococcosis, CNS tuberculosis and immune reconstitution inflammatory syndrome (IRIS). Each condition shows certain specific MRI features which aid in diagnosis. Although, distinguishing between HIV-related CNS diseases based on imaging alone is sometimes difficult, in this review, we discuss the spectrum and imaging features that can contribute to their early differentiation.